Activation of the MoSe2 basal plane and Se-edge by B doping for enhanced hydrogen evolution. Issue 2 (12th December 2017) - Gao, Daqiang; Xia, Baorui; Zhu, Changrong; Du, Yonghua; Xi, Pinxian; Xue, Desheng; Ding, Jun; Wang, John
Abstract : We demonstrate by both calculation and experiments the effective B doping-induced activation of both the basal plane and Se-edge in vertically aligned MoSe2 flakes, and the disruptive enhancement in the electrocatalytic hydrogen evolution reaction. Abstract : We demonstrate by both calculation and experiments the effective B doping-induced activation of both the basal plane and Se-edge in vertically aligned MoSe2 flakes, and the disruptive enhancement in the electrocatalytic hydrogen evolution reaction. The B doping boosts drastically the catalytic activity of MoSe2 for the hydrogen evolution reaction compared to the undoped one, characterized by a low overpotential (84 mV) and Tafel slope (39 mV s −1 ), which are comparable to those of the best Pt/C electrode. The realization of activation for both the basal plane and Se-edge by B doping in MoSe2 shows an innovative pathway towards the activity enhancement of TMDs for electrocatalysts and energy storage.